Binary Mixtures of Proton-Conducting Ionic Liquids as Electrolytes for Medium-Temperature Polymer Electrolyte Membrane Fuel Cells - Suo, Yanpeng; Hou, Hui; Lin, Jingjing; Chen, Yingzhen; Liu, Chang; Wang, Ce; Schulz, Peter; Wippermann, Klaus; Korte, Carsten (Journal of Physical Chemistry C, 2021)
In this study, physicochemical and electrochemical characterization of mixtures of proton-conducting ionic liquids (PILs) is reported for potential future use as a novel electrolyte in polymer electrolyte membrane fuel cells operable at 100-120 °C. By blending two PILs, 2-sulfoethyl-methyl-ammonium triflate [2-Sema][TfO] and diethyl-methyl-ammonium triflate [Dema][TfO], exhibiting different cation acidities and different oxygen diffusivities/solubilities, it was apparent that the superior physicochemical and electrochemical properties of both PILs can be favorably combined. Improved thermal stability of the blend, compared to neat [2-Sema][TfO], was observed. The viscosity of the mixtures decreased when increasing the fraction of [Dema][TfO], which led to increased proton conductivity and oxygen transmission coefficients, that is, D × c. In combination with the highly acidic [2-Sema]+ cations, which served as strong proton donors for the oxygen reduction reaction (ORR), it led to an increase in the ORR limiting current density at cell potentials relevant for fuel cell operation.
CRIS-Team Scopus Importer:2021-10-29